Effect of drought and nitrogen fertilisation on quinoa (Chenopodium quinoa Willd.) under field conditions in Burkina Faso - Alvar-Beltrán, Jorge; Saturnin, Coulibaly; Dao, Abdalla; Dalla Marta, Anna; Sanou, Jacob; Orlandini, Simone (Italian Journal of Agrometeorology, 2019)
Chenopodium quinoa (Willd.) is an herbaceous C3 crop originating in the Andean Altiplano. Quinoa possesses a great deal of genetic variability, can adapt to diverse climatic conditions, besides of having seeds with high nutritional properties. An experiment conducted in Burkina Faso has determined the response of two quinoa varieties (Titicaca and Negra Collana) to different planting dates (November vs December), irrigation levels (Potential evapotranspiration-PET, 100, 80 and 60% PET), and N fertilization rates (100, 50 and 25 kg N ha-1). Main research findings have shown that quinoa can be highly performant under drought stress conditions and low nitrogen inputs, besides of coping with high temperatures typically of the Sahel. The highest yields (1.9 t ha-1) were achieved when sown in November at 60 % PET and 25 kg N ha-1. For this location, short cycle varieties, such as Titicaca, were recommended in order to avoid thermic stress conditions occurring prior to the onset of the rainy season (May-October).